Analysis of process parameters effects on underwater friction stir welding of aluminum alloy 6082-T6. (May 2019) - Wahid, Mohd Atif; Khan, Zahid A; Siddiquee, Arshad Noor; Shandley, Rohit; Sharma, Nidhi
In friction stir welding of heat treatable aluminum alloys, the thermal cycles developed during the joining process result in softening of the joints which adversely affect their mechanical properties. Underwater friction stir welding can be a process of choice to overcome this problem due to low peak temperature and short dwell time involved during the process. Consequently, this article presents a study pertaining to the underwater friction stir welding of aluminum alloy 6082-T6 with an aim to develop a mathematical model to optimize the underwater friction stir welding process parameters for obtaining maximum tensile strength. The results of the study reveal that the tool shoulder diameter (d), tool rotational speed (ω), welding speed (v), and second-order term of rotational speed, that is, ω 2, significantly affect the tensile strength of the joint. The maximum tensile strength of 241 MPa which is indeed 79% of the base metal strength and 10.7% higher than that of conventional (air) friction stir welding joint was achieved at an optimal setting of the underwater friction stir welding parameters, that is, tool rotational speed of 900 r/min, the welding speed of 80 mm/min, and a tool shoulder of 17 mm. The article also presents the results of temperature variation, the macrostructural and microstructural investigations, microhardness, and fractography of the joint obtained at the optimal setting for underwater friction stir welded (UFSWed) joint.